Interactive Learning Media Oriented Problem-Based Learning to Improve Students Mathematical Problem Solving Skills - Pratiwi, Kadek Ayu Mutiara; Suharta, I Gusti Putu; Suparta, I Nengah (Thinking Skills and Creativity Journal, 2024)
The importance of using learning media in mathematics learning so that learning is more interesting has not been optimized, learning is still conventional which affects the low ability to solve students' mathematical problems. This research develops interactive learning media oriented to Problem-Based Learning designed to improve students' mathematical problem-solving skills. The research procedure used is the procedure from Plomp which consists of 3 phases, namely, the Preliminary Research Phase, the Prototyping Phase, and the Assessment Phase. The subjects of the study were two validators, as well as 26 students in the limited trial, 35 students in field trial I, and as many as 43 students in field test II. The result of the product is an interactive learning media oriented to problem-based learning that is of valid, practical, and effective quality. Product quality obtained an average score of 3.60 with a very valid category, practical quality in terms of student response, teacher response, and media implementation in classroom learning, and effective quality in improving students' mathematical problem-solving skills as evidenced by gain-score with a fairly effective category.